1994
DOI: 10.2737/pnw-gtr-320
|View full text |Cite
|
Sign up to set email alerts
|

Fire and weather disturbances in terrestrial ecosystems of the eastern Cascades.

Abstract: Fire has been an important ecological process in eastside Cascade ecosystems for millennia. Fire regimes ranged from low severity to high severity, and historic fire return intervals ranged from less than a decade to greater than 300 years. Fire history and effects are described for grassland and shrubland ecosystems, and the range of forested communities by plant series: Ponderosa Pine, Douglas-fir/White fir/Grand fir, Lodgepole pine, Western hemlock/Western redcedar, and subalpine fir/Mountain hemlock. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 83 publications
1
108
1
2
Order By: Relevance
“…In general, the influence of topography on burn severity is greater on steep slopes, ridgetops, and southerly aspects [20,33,71]. Thus, it is generally assumed that burn severity is higher at higher than at lower elevations, and many studies have reported a strong positive association between burn severity and elevation.…”
Section: Elevation Groupmentioning
confidence: 99%
“…In general, the influence of topography on burn severity is greater on steep slopes, ridgetops, and southerly aspects [20,33,71]. Thus, it is generally assumed that burn severity is higher at higher than at lower elevations, and many studies have reported a strong positive association between burn severity and elevation.…”
Section: Elevation Groupmentioning
confidence: 99%
“…Fire suppression and insect outbreaks in the last 25 years have resulted in high fuel loadings in some stands in northeastern Oregon (Agee 1994). The risk of wildfire in these stands has generated concern among managers, and various methods of removing some of these fuels are being used.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use practices over the last 100 years have altered the natural disturbance regime and reduced ecosystem resistance to disturbances. Fire suppression, timber harvest, and livestock grazing are among the management practices that have contributed to changes in ecosystem character that are conducive to insect outbreaks and severe wildfires (Agee 1993, Gast and others 1991, Hessburg and others 1993, Martin and others 1976 (fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Surface fires tend to occur in dry and warm vegetation series, such as ponderosa pine 1 and dry Douglas-fir series, at relatively frequent intervals of 3 to 35 years (see Agee 1993 for review). These low-intensity fires influence vegetation composition and structure primarily at a stand scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation